Analysis of student’s creative thinking ability in computation physics course - Rizka Melia Putri; Akmam Akmam; Fatni Mufit; Silvi Yulia Sari; Rahmat Hidayat (Universitas Sultan Ageng Tirtayasa, 2022)
Creative thinking is a crucial thing to support the development of students taking Computational Physics courses but is rarely considered, so it takes a description of students' creative thinking skills so as to provide alternative appropriate learning methods. The purpose is to determine the ability of creative thinking of college students within the Computational Physics courses. This kind of study is descriptive with a quantitative method. The studies populace is all college students taking courses of Computational Physics for the January-June 2021 semester. The studies tool is within the form of a questionnaire. The research results: Students' Creative Thinking Ability in Computational Physics Course as a whole is 65%, based on the Problem Sensitivity indicator has a direct effect value of 0.91, the Fluency indicator is 0.94, the Flexibility indicator is 0.96, the Originality indicator is 0.64, the Elaboration indicator is 0.69, and the Evaluation indicator 0.58.